"I feel your disgust and relief": can the action understanding system (mirror neuron system) be recruited to induce disgust and relief from contamination vicariously, in individuals with obsessive–compulsive disorder symptoms?. Issue 1 (2nd January 2017) - Jalal, Baland; Ramachandran, Vilayanur S.
ABSTRACT: Research has shown that brain regions mediating disgust (e.g., the insula) become activated when viewing others' disgust, a response mediated, perhaps by the mirror neuron system or the Theory of Mind module. In a novel behavioral experiment, we explore vicarious disgust and relief, in individuals with obsessive–compulsive disorder (OCD) symptoms. Participants ( N  = 10) provided disgust ratings to self-contamination or watching the contamination of an experimenter; and to the experimenter washing his own hands after the subjects had been contaminated. To our surprise, we found that subjects experienced disgust from merely watching the experimenter contaminating himself. More intriguingly, after subjects had contaminated themselves, they obtained relief from merely watching the experimenter washing his own hands; even while recognizing the logical absurdity of this. The result is counterintuitive since neither the subjects nor anyone else would have predicted this. These preliminary findings – if confirmed in placebo-controlled studies – might pave the way toward novel therapeutic approaches for OCD.